Islamic Religious Education Strategy for Children with Visual Impairments - Andini Andini; Difa'ul Husna (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2023)
The learning strategy aims to realize the efficiency and effectiveness of teaching and learning activities for students, including children with special needs for the visually impaired. Teachers must strive so that students can receive the material well using the right strategy. This research aimed to determine the learning strategy of Islamic religious education for visually impaired children with special needs at SLB Negeri Banjarnegara and determine the supporting and inhibiting factors in the learning process of Islamic religious education. The research uses a qualitative research approach. Data were collected through observation to obtain sufficient data. Then conducted, interviews with related parties to support the data. Documentation is carried out for the data to be more valid. After all the data has been collected, data analysis is carried out by reducing the data, presenting the data and drawing conclusions. The results of this study showed that the learning strategy of Islamic religious education, which was applied to children with visual impairments at SLB Negeri Banjarnegara, used direct instruction strategies by applying lecture, discussion, and question-and-answer methods.